Analysis of Factors Affecting the Occurrence of Ectopic Pregnancy: Risk Factors, Early Detection, and Preventive Strategies - Iroh, Nadhifa; Nuraini, Diva Novita (International Journal on ObGyn and Health Sciences, 2025)
Ectopic pregnancy is a leading cause of maternal morbidity and mortality, with several factors contributing to its occurrence. This research aims to analyze the causes and risk factors associated with ectopic pregnancy, focusing on tubal factors, hormonal imbalances, infections, previous surgeries, age, smoking, contraceptive use, and obesity. A comprehensive review of existing literature was conducted, and primary data was collected through surveys and medical records analysis. The study found that tubal factors, pelvic inflammatory disease, and previous surgeries were the most significant risk factors. Additionally, obesity, smoking, advanced maternal age, and contraceptive use, especially IUDs, were identified as contributing factors. Unexpectedly, emotional stress was found to have a notable association with ectopic pregnancy. The findings suggest the need for public health interventions focusing on lifestyle changes, mental health support, and patient education about contraceptive risks. Preventive strategies such as early screening for high-risk individuals, stress management, and enhanced contraceptive counseling are recommended. Future research should explore the psychological aspects of ectopic pregnancy, the impact of obesity on reproductive health, and the development of improved detection methods and guidelines for contraceptive use.